The determinants of multiple sexual partnerships among men in Zimbabwe - Mutenheri, Enard (My University, 2012)
Introduction The burden of HIV/AIDS is higher in the sub-Saharan region and multiple sexual partnerships are among the sexual behaviors that put people at risk of HIV transmission. The main aim of this study was to determine the prevalence and associated demographic, socio-economic and behavioral factors of multiple sexual partnerships among men in Zimbabwe. Materials and Methods This was an analytical cross-sectional study that used data from the Zimbabwe Demographic Health Survey 2005-06. Negative binomial regressions were fitted to identify factors associated with multiple sexual partnerships among men in Zimbabwe. Results The prevalence of multiple sexual partnerships was 13.5 %, 12.9%, and 11.2% among the formerly, never and currently married men respectively. Among the formerly married men, the risk factors significantly associated with multiple sexual partnerships included access to newspapers (RR= 1.28; 95% CI:1.02 , 1.60). Formerly married men aged 35-44 years had lower risk of engaging in multiple sex partnerships (RR = 0.59, 95%CI: 0.42, 0.83) than the other age groups. Relative to formerly married men in Manicaland, formerly married men in Mashonaland East region had lower risks of having more sexual partners. Age at first intercourse and sexual attitude were also significantly associated with multiple sexual partnerships among the formerly married men iv Among the never married men, the risk factors associated with multiple sexual partnerships included employment status (RR = 1.33%; 95%CI: 1.17, 1.52), Watching TV (RR = 1.33%; 95%CI: 1.05, 1.69) and sexual attitude (RR = 1.37%; 95% CI: 1.05, 1.79). Relative to never married men in Manicaland, the never married men in Mashonaland East and Mashonaland West had lower risks of having multiple sexual partners. Among the married men, the risk factors associated with multiple sexual partnerships included first intercourse at the age of 19 years or below (RR = 1.07%; 95% CI: 1.04, 1.11) and sexual attitude (RR = 1.16%; 95% CI: 1.09, 1.23). Protective factors included higher level of education (RR = 0.87%; 95% CI: 0.77, 0.98), being 35-44 (RR = 0.94%; 95% CI: 0.89, 0.99) or 45-54 years old (RR = 0.93%; 95% CI: 0.88, 0.99) and being from Mashonaland East (RR= 0.89%; 95%CI: 0.85, 0.93) region. Discussion and Conclusions The results show that after adjusting for potential confounders in the multivariate negative binomial regression analysis; age, geographical region, education, working status, frequency of reading newspapers/magazines/TV, age at first intercourse and sexual attitude remained significantly associated with MSP. However, the extent to which each of these factors was associated with multiple sex partnership varied among marital status groups, therefore HIV/AIDS intervention programs should be designed accordingly.
A research report submitted to the Faculty of Health sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Medicine in Epidemiology and Biostatistics 30th May 2012
Keywords: HIV Infection; Sexual Partners